ECOLOGICAL STUDIES ON NEPENTHES AT BARITO ULU, CENTRAL KALIMANTAN, INDONESIA - Muhammad Mansur (Jurnal Teknologi Lingkungan, 2008)
Ecological studies on the Nepenthes species at Barito Ulu, Central Kalimantan, Indonesia were conducted between August 2005 and September 2006. Surveys and two small plot inventories were used to determine the diversity and population of Nepenthes at the study site. We found eight Nepenthes species around the BaritoUlu study area: N. albomarginata, N. ampullaria, N. gracilis, N. hirsuta, N. rafflesiana, N. reinwardtiana, N. stenophylla, and N. hispida. Plot A was dominated by N. rafflesiana with one other species found; whilst in plot B we found five species but it was also dominated by N. rafflesiana. In plot A, the one year stem length growth rate of N. albomarginata was faster than N. rafflesiana (5.0 and 3.5 cm respectively). While in plot B, N. gracilis (21.7 cm) and N. reinwardtiana (13.1 cm) showed faster growth rates than N. albomarginata (5.2 cm), N. rafflesiana (7.0 cm) and N. stenophylla (8.5 cm). Generally, the habitat of Nepenthes in the study site is heath forest.